KELUARGA BROKEN HOME DAN DAMPAKNYA TERHADAP KESEHATAN MENTAL SISWA DI SMP NEGERI 3 MESUJI LAMPUNG - muhammad mitra (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
A broken home family is a situation in a family where there is no harmony, so thaunfavorable circumstances arise and do not provide a sense of comfort in the family. The aim of this research is to find out the causes of broken homes at SMP Negeri 3 Mesuji, to find out the influence of broken home families on the mental health of students at SMP Negeri 3 Mesuji, and to find out the impact of broken homes on the mental health of students at SMP Negeri 3 Mesuji. The research method used in this research is qualitative research. The subjects of this research were Counseling Guidance Teachers, Students, and parents of SMP Negeri 3 Mesuji. The data collection process in this research was carried out through the process of Observation, Interview, and Documentation (taking pictures). The techniques used for data analysis in this research are reducing data, presenting data, and drawing conclusions. The results of this research show that the causes of broken homes among students' parents at SMP Negeri 3 Mesuji Lampung are lack of love, economic problems, divorce and the death of their father or mother. Broken home families have an influence on students' mental health. The treatment is to provide understanding, always participate in activities so that the child blends in with the surrounding community, and must pay more attention to the child. And the impact of mental health on students has positive and negative impacts that appear on the child's psyche. The positive impact of children experiencing a broken home is that children become independent and strong. Meanwhile, the negative impact of children experiencing a broken home turns out to have a huge impact on children's mental health, because children will do negative things to get attention from their parents. Advice to parents to always pay attention to harmonious family relationships and to students who are affected by broken homes so that they are better able to control themselves.